Concentration Conditions of Carbon Dioxide in Bukittinggi During the Event of El Niño 2015 - Martono Martono; Ninong Komala (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2018)
In 2015, about 2.61 million ha of land and forests in Indonesia were on fire and indicated will increase the amount of CO2 emitted into the atmosphere. The purpose of this study was to understand the condition of CO2 concentration at Bukittinggi during El Niño 2015. The data used was the data of Kototabang CO2 concentration, NINO3.4 index and chlorophyll-a concentration from 2004-2016. The results showed that CO2 concentration at Bukittinggi from 2004-2016 was increased of about 2.4 ppm/year. CO2 concentration in the first transition season (March-May) and the east season (June-August) 2015 were approximately 397 and 395 ppm, respectively, lower than that in 2016 on the same months which was about 401 and 397 ppm, respectively. In the second transition season (September-November) in 2015, CO2 concentration reached 401 ppm which was higher than that in 2016 which was only 397 ppm. In 2015, chlorophyll-a concentration in the southern waters of Java increased about 14% in the east season and reached 50% during the second transition season. Therefore, small increase of CO2 concentration during El Niño 2015 was indicated as a result of high uptake of CO2 by the sea for photosynthesis needs.